Deteksi Bakteri Proteolitik Dari Ileum Gallus Gallus Sebagai Kandidat Agen Probiotik Pakan Fermentasi Unggas - Tengku Gilang Pradana; Alfath Rusdhi; Indah Pratiwi Purba (Journal of Pharmaceutical and Sciences, 2023)
The ileum is part of the small intestine that functions as the absorption of food and for the growth and development of bacteria to degrade feed, such as lactic acid bacteria. The purpose of this study was to explore and detect proteolytic bacteria from the ileum of Gallus gallus as a candidate probiotic agent. The research method is a selection of proteolytic bacteria, catalase, and motility. The results showed that the average proteolytic index in isolates GP sp. 4, GP sp.3, and GP sp. 1 were 1.533, 1.531, and 1.500. Nine isolates were gram-positive and one gram-negative (GP sp. 3). The ten isolates could hydrolyze hydrogen peroxide, as indicated by the formation of air bubbles. The motility test showed that eight isolates were motile and the other two isolates were non-motile (GP sp.8 and GP sp.10). The ten proteolytic bacterial isolates obtained did not have the potential to be used as probiotic agents for fermented poultry feed because low proteolytic index value.